Curative treatment for low-grade arteriovenous malformations. (12th July 2019) - Wang, Arthur; Mandigo, Grace K; Feldstein, Neil A; Sisti, Michael B; Connolly, E Sander; Solomon, Robert A; Lavine, Sean D; Meyers, Philip M
Abstract : Background: Spetzler-Martin (SM) grade I-II (low-grade) arteriovenous malformations (AVMs) are often considered safe for microsurgery or radiosurgery. The adjunctive use of preoperative embolization to reduce surgical risk in these AVMs remains controversial. Objective: To assess the safety of combined treatment of grade I-II AVMs with preoperative embolization followed by surgical resection or radiosurgery, and determine the long-term functional outcomes. Methods: With institutional review board approval, a retrospective analysis was carried out on patients with ruptured and unruptured SM I-II AVMs between 2002 and 2017. Details of the endovascular procedures, including number of arteries supplying the AVM, number of branches embolized, embolic agent(s) used, and complications were studied. Baseline clinical and imaging characteristics were compared. Functional status using the modified Rankin Scale (mRS) before and after endovascular and microsurgical treatments was compared. Results: 258 SM I-II AVMs (36% SM I, 64% SM II) were identified in patients with a mean age of 38 ± 17 years. 48% presented with hemorrhage, 21% with seizure, 16% with headache, 10% with no symptoms, and 5% with clinical deficits. 90 patients (68%) in the unruptured group and 74 patients (59%) in the ruptured group underwent presurgical embolization (p = 0.0013). The mean number of arteries supplying the AVM was 1.44 and 1.41 in the unruptured and ruptured groups, respectively (p = 0.75). The mean number of arteries embolized was 2.51 in the unruptured group and 1.82 in the ruptured group (p = 0.003). n-Butyl cyanoacrylate and Onyx were the two most commonly used embolic agents. Four complications were seen in four patients (4/164 patients embolized): two peri-/postprocedural hemorrhage, one dissection, and one infarct. All patients undergoing surgery had a complete cure on postoperative angiography. Patients were followed up for a mean of 55 months. Good long-term outcomes (mRS score ≤ 2) were seen in 92.5% of patients with unruptured AVMs and 88.0% of those with ruptured AVMs. Permanent neurological morbidity occurred in 1.2%. Conclusions: Curative treatment of SM I-II AVMs can be performed using endovascular embolization with microsurgical resection or radiosurgery in selected cases, with very low morbidity and high cure rates. Compared with other published series, these outcomes suggest that preoperative embolization is a safe and effective adjunct to definitive surgical treatment. Long-term follow-up showed that patients with low-grade AVMs undergoing surgical resection or radiosurgery have good functional outcomes.